1997
DOI: 10.1152/jappl.1997.83.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Purified ACE attenuates smokeless tobacco-induced increase in macromolecular efflux from the oral mucosa

Abstract: Purified ACE attenuates smokeless tobacco-induced increase in macromolecular efflux from the oral mucosa. J. Appl. Physiol. 83(1): 74-81, 1997.-The purpose of this study was to determine whether purified angiotensin I-converting enzyme (ACE) attenuates smokeless tobacco extract (STE)-induced increase in macromolecular efflux from the in situ oral mucosa. By using intravital microscopy, we found that suffusion of an aqueous extract of smokeless tobacco elicited significant concentration-dependent leaky site fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…First, we found that exposure of HCPC-1 to aqueous STE, at noncytotoxic concentrations that have been previously shown to evoke inflammation in the in situ hamster cheek pouch (11,12), together with VIP, a ubiquitous autocrine neuropeptide in the oral epithelium (17), is associated with significant, concentration-dependent, synergistic increase in DNA synthesis as assessed by BrdU incorporation. These effects were mediated by VIP receptors because VIP 10-28 , a VIP receptor antagonist in the in situ hamster cheek pouch (43), but not VIP [1][2][3][4][5][6][7][8][9][10][11][12] , an inactive peptide fragment (43), significantly attenuated VIP-induced increase in DNA synthesis in the absence or presence of STE. Second, STE inactivated NEP 24.11, an ectoenzyme widely distributed in oral epithelium that cleaves and inactivates VIP very effectively (12,35,43,52), in HCPC-1 cells after 48-h incubation, a time when VIP-induced DNA synthesis was maximal.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…First, we found that exposure of HCPC-1 to aqueous STE, at noncytotoxic concentrations that have been previously shown to evoke inflammation in the in situ hamster cheek pouch (11,12), together with VIP, a ubiquitous autocrine neuropeptide in the oral epithelium (17), is associated with significant, concentration-dependent, synergistic increase in DNA synthesis as assessed by BrdU incorporation. These effects were mediated by VIP receptors because VIP 10-28 , a VIP receptor antagonist in the in situ hamster cheek pouch (43), but not VIP [1][2][3][4][5][6][7][8][9][10][11][12] , an inactive peptide fragment (43), significantly attenuated VIP-induced increase in DNA synthesis in the absence or presence of STE. Second, STE inactivated NEP 24.11, an ectoenzyme widely distributed in oral epithelium that cleaves and inactivates VIP very effectively (12,35,43,52), in HCPC-1 cells after 48-h incubation, a time when VIP-induced DNA synthesis was maximal.…”
Section: Discussionmentioning
confidence: 85%
“…Section 1734 solely to indicate this fact. previously described (11,12,27,37). Briefly, 10 g of smokeless tobacco (1S3 moist snuff; Tobacco and Health Research Institute, University of Kentucky, Lexington, KY) were mixed with 100 ml DMEM and incubated at 37°C for 2 h. The mixture was then centrifuged at 450 g for 10 min.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…In preliminary studies, I determined that suffusion of aprotinin (5 g/ml) and leupeptin (10 g/ml) alone for 30 min was associated with no visible leaky site formation or increase in the clearance of FITC-dextran (data not shown). The concentrations of aprotinin and leupeptin used in these studies were based on previous studies in my laboratory and on reports in the literature (2,9,13,17,18,22,31,38).…”
Section: General Methods (I) Preparation Of Animalsmentioning
confidence: 99%